7-5(4x-2)=(-83)

Simple and best practice solution for 7-5(4x-2)=(-83) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7-5(4x-2)=(-83) equation:



7-5(4x-2)=(-83)
We move all terms to the left:
7-5(4x-2)-((-83))=0
We add all the numbers together, and all the variables
-5(4x-2)+90=0
We multiply parentheses
-20x+10+90=0
We add all the numbers together, and all the variables
-20x+100=0
We move all terms containing x to the left, all other terms to the right
-20x=-100
x=-100/-20
x=+5

See similar equations:

| 110x+30(+0,5x)+80(0,25x)=26100 | | x+(29+x)+(26+x)=100 | | (29+x)+(26+x)=100 | | -33/9=-6x+22/3 | | x(x-14)=5880 | | 17x-45=-11 | | -1.3+10(x+10)=4-5(2x+11) | | -3x/5-4=10 | | (3n+6)(2n-6)=0 | | (3n+6)(2n–6)=0 | | -1.4+10(x+10)=4-5(2x+11) | | (20+x)+20=500 | | (1/2x)+x+60=180 | | 1.7x+8.4x=7.2+7.8x | | 2^2t-12(2^t)+32=0 | | (x+17)+(4x-5)=117 | | -4x-151=3x+87 | | -2(3x-5)=4(3x+2)-8x | | 6x2−17x+14=0 | | Y-5=-4(x+3) | | 3(2x-7)=(-33) | | -60+8x=14x+102 | | 9−−18÷−2=x | | 3(y+1)=7.5 | | 3(p+7)=9 | | Y=-0.02d²+2.6d-66.5 | | 2^t-12(12t)+32=0 | | v^2=10 | | 15y=60-18× | | (3x)+21=3(x+7) | | 5(4^x)=30 | | 3-4y=5y-15 |

Equations solver categories